Adsorpsi Biocharcoal Kulit Durian (Durio zibethinus Murr) Terhadap Ion Kadmium - Kusuma, I Gede Yoga Nata; Napitupulu, Mery; Walanda, Daud K. (Jurnal Akademika Kimia, 2015)
Research on the adsorption biocharcoal of durian (durio zibethinus murr) bark to cadmium ion has been conducted. Heavy metal ions are toxic and generally as a major pollutant to the environment. Handling of waste containing heavy metal ions, especially Cd2+ ions have been carried out and need to be developed. This study described the ability of biocharcoal (biological charcoal) of durian bark to adsorb Cd2+ ions from their solutions. The method in this study was a laboratory experiment using biological charcoal powder of durian bark as an adsorbent of Cd2+ ions. Concentration of Cd2+ ions absorbed was measured using atomic absorption spectrophotometer (AAS) at a wavelength of 228.8 nm. The results showed the optimum Cd2+ ion absorbed was at 80 mg biocharcoal with the percentage of the Cd2+ ion absorbed up to 93.46%, where the weight of the Cd2+ ion absorbed was 16.62 mg/g. The optimum pH was at 7.0 with the percentage of the Cd2+ ion absorbed up to 97.94%, where the weight of the Cd2+ ion absorbed was 17.42 mg/g. The optimum concentration was at 20 ppm with the percentage of the Cd2+ ion absorbed up to 91.97%, where the weight of Cd2+ ion absorbed was 11.42 mg/g. The maximum absorption capacity of biocharcoal to the Cd2+ ion using the Langmuir isotherm adsorption equation was 33.33 mg/g of biocharcoal.